The practices of Pedagogical Methods for children with ASD (Research, Society and Development, 2021)
This article aims to present the possible Stages of the Autistic Spectrum Disorder (ASD), the Pedagogical Practices, and the Methods for the early development and Intervention of the child with ASD. Emphasizing the importance of the Psychopedagogist (a) in the process of these practices and the DUSNST & BRUDER (2002) intervention, demystifying the social imaginary, which describes that such a child cannot develop, and the non-existence of resources/tools to be used in your favor. In this context, the research is characterized as bibliographical, with an exploratory character. Evidencing that the recognition of the ASD, as well as the pedagogical practices and methods, are crucial for a comprehensive development and significant actions in the life of a child with ASD, not forgetting that the family is a fundamental part for the inclusion of the child with ASD in all the spheres of society. Thus, we seek to answer, through this research, questions related to the lack of resources, to evolve the child with Autism Spectrum Disorder (ASD) in the educational sphere.